Preoperative plasma visfatin may have a dual effect on the occurrence of postoperative delirium - Kang, Ning; Yang, Ning; Zhao, Kaixuan; Li, Zhengqian; Zhang, Wenchao; Han, Yongzheng; Liu, Kaixi; Song, Yanan; Chen, Lei; Li, Yue; Hong, Jingshu; Li, Yitong; et al. (Frontiers in Medicine, 2022)
Background: Visfatin is considered to be a “novel pro-inflammatory cytokine.” Neuroinflammatory response is one of the important mechanisms of postoperative delirium (POD). The relationship between preoperative plasma visfatin and POD is unclear. Objective: To investigate the relationship between preoperative plasma visfatin concentrations and POD (primary outcome) in older hip fracture patients and to explore whether it affects POD through inflammatory factors. Materials and Methods: This prospective cohort study enrolled 176 elderly patients who were scheduled for hip fracture surgery. Preoperative plasma was collected on the morning of surgery, and visfatin levels were measured. Interleukin (IL)-1 and IL-6 were measured using patients’ plasma collected on the first day after surgery. We used the 3-minute diagnostic interview for Confusion Assessment Method-defined delirium(3D-CAM) twice daily within the 2 days after surgery to assess whether POD had occurred. Restricted cubic splines and piecewise regression were used to explore the relationship between preoperative plasma visfatin concentrations and POD, and further mediation analysis was used to verify whether visfatin plays a role in POD through regulating inflammatory factors. Results: The incidence of POD was 18.2%. A J-shaped association was observed between preoperative plasma visfatin levels and POD. The risk of POD decreased within the lower visfatin concentration range up to 37.87 ng/mL, with a hazard ratio of 0.59 per 5 ng/mL (odds ratio [OR]=0.59, 95% confidence interval [CI]=0.37–0.95), but the risk increased above this concentration (P for non-linearity <0.001, with a hazard ratio of 1.116 per 10 ng/mL; OR=1.10, 95%CI=1.02–1.23). Mediation effect analysis showed that when the plasma visfatin concentration was higher than 37.87 ng/mL, the effect of visfatin on POD was mediated by IL-6 (p<0.01) . A signifificant indirect association with postoperative plasma IL-6 was observed between preoperative plasma visfatin and POD (adjusted β= 0.1%; 95% CI= 4.8% 38.9%; p<0.01) Conclusion: Visfatin is the protective factor in POD when the preoperative plasma visfatin concentration is below 37.87 ng/mL, but when it exceeds 37.87 ng/mL, the visfatin concentration is a risk factor for POD, which is mediated by postoperative plasma IL-6. The results suggest that preoperative visfatin may have a dual effect on the POD occurrence.